Evaluation of myocardial blood flow and coronary flow reserve — the physiological foundation and clinical significance of myocardial perfusion scintigraphy in the examination of patients with chronic coronary syndrome - A. V. Mochula; A. N. Maltseva; V. V. Shipulin; K. V. Zavadovsky (Российский кардиологический журнал, 2020)
Non-invasive cardiovascular imaging plays an important role in examination of patients with chronic coronary syndrome. Positron emission tomography (PET) has the highest diagnostic accuracy and prognostic significance due to the ability to assess myocardial blood flow (MBF) and coronary flow reserve (CFR). These physiological processes provide myocardial oxygen demand, both at rest and stress, as well as maintaining sufficient myocardial circulation during coronary artery constriction. At the same time, the high cost and low availability of assessing MBF and CFR by PET do not allow widespread use of this approach in clinical practice. The use of modern gamma cameras with cadmium zinc telluride detectors can be an alternative to PET. The aim of the review is to present fundamental information about MBF and CFR, as well as about the possibilities of using scintigraphy for determination of these parameters and their clinical significance.